Stent-Jailing Technique Reduces Aneurysm Recurrence More Than Stent-Jack Technique by Causing Less Mechanical Forces and Angiogenesis and Inhibiting TGF-β/Smad2,3,4 Signaling Pathway in Intracranial Aneurysm Patients - Xu, Ning; Meng, Hao; Liu, Tianyi; Feng, Yingli; Qi, Yuan; Zhang, Donghuan; Wang, Honglei (Frontiers in Physiology, 2019)
Background Stent-jailing and stent-jack are used for stent-assisted coil embolism (SCE) in intracranial aneurysm (IA) therapy, and cause different incidences of IA recurrence. Angiogenesis strongly correlates with aneurysm accumulation. Stent-jack causes higher mechanical forces in cerebral vessels than stent-jailing. Mechanical forces, as well as TGF-β/Smad2,3,4 signaling pathway, may play an important factor in IA recurrence by affecting angiogenesis. Methods We explored the effects of stent-jailing or stent-jack technique on IA recurrence by investigating mechanical forces, TGF-β/Smad2,3,4 signaling pathway and the incidence of angiogenesis in IA patients. One-hundred-eighty-one IA patients were assigned into stent-jailing (n = 93) and stent-jacket groups (n = 88). The clinical outcome was evaluated using Glasgow Outcome Score (GOS) and aneurysm occlusion grades. The percentage of CD34+EPCs (releasing pro-angiogenic cytokines) in peripheral blood was measured by flow cytometer. Endothelial cells were separated from cerebral aneurysm and malformed arteries via immunomagnetic cell sorting. Angiogenesis was measured by microvessel density (MVD) using anti-CD34 monoclonal antibody staining before using the stent, immediately after surgery and two years later. Meanwhile, the mechanical forces in cerebral vessels were determined by measuring endothelial shear stress (ESS) via a computational method. TGF-β and Smad2,3,4 were measured by real-time qPCR and Western Blot. Tube formation analysis was performed to test the relationship between angiogenesis and TGF-β, and the effects of different techniques on angiogenesis. Results After a two-year follow-up, 85 and 81 patients from stent-jailing and stent-jack groups, respectively, completed the experiment. Stent-jailing technique improved GOS and reduced aneurysm occlusion grades higher than the stent-jack technique (P < 0.05). The counts of CD34+EPCs and MVD values in the stent-jailing group were lower than the stent-jack group (P < 0.05). ESS values in sent-jailing group were lower than the stent-jack group (P < 0.05), and positively correlated with MVD values (P < 0.05). TGF-β and Smad2,3,4 levels in sent-jailing group were also lower than the stent-jack group (P < 0.05). TGF-β was associated with angiogenesis incidence and stent-jack caused angiogenesis incidence more than stent-jailing. Conclusions Stent-jailing technique reduces IA recurrence more than stent-jack by causing less mechanical forces, angiogenesis and inhibiting TGF-β/Smad2,3,4 signaling in IA patients.